Effect of Teaching Methods on Students' Academic Performance in Chemistry in Nigeria: Meta-Analytic Review - E.N. Okwuduba; E.C. Okigbo (University of Sofia, 2018)
A lot of research studies have been conducted on effects of teaching methods on academic performance of students and they proved to be significant. But there is a discordant view on their results. This study uses meta-analytic review to harmonize studies conducted in Nigeria from 1990 to 2010 on effect of teaching method on students' academic performance in chemistry. This quasi experimental review was carried out under six phases namely; collection of the study, coding of the study, determination of inter-raters reliability, setting a benchmark for selecting a study, calculation of effect sizes and carrying out analysis. The required research studies must have statistics descriptions for computation of effect size. Fifty-one research works were sampled and used because they met the benchmark set for selection. Seven classes of teaching method were identified and they include: mastery learning (-0.013), Computer Assisted Instruction (0.146), Instructional Materials (0.208), Problem solving (0.315), Constructivist/concept mapping (-0.203), games/simulation/animations (0.173), student grouping/cooperative learning (0.218). The overall effect size is 0.147. The significant variations in the magnitude of effect sizes were resolved to some extent by application of random-model effect size meta-analytic technique. The major implication of this review is that we generated the most effective method of teaching chemistry.